Can't Work From Home: Pooled Nucleic Acid Testing of Laboratory Workers During the COVID-19 Pandemic. (15th March 2021) - Rawlings, Stephen A; Scott, Brianna; Layman, Laura; Naranatt, Pramod; Heltsley, Roy; Ignacio, Caroline; Porrachia, Magali; Gianella, Sara; Smith, Davey; Chaillon, Antoine
Abstract: Together with protective measures, routine screening for severe acute respiratory syndrome coronavirus 2 infection helps provide a safe working environment. We evaluated a pooled nucleic acid testing strategy in a research laboratory. It allowed lab activity to be maintained and would save 25 920 person-hours and $1 684 800/year by increasing the margin of safety for returning to work.